Disaster Risk Mapping of Village Tourist Attractions in an Effort to Improve Safety and Comfort - Yusuf Adam Hilman; Shahrum Shah Abdullah; Deny Wahyu Tricana; Meilia Gita Saskia; Larasati Kansa Widya Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Cleanliness, comfort, and safety are essential factors that must be met to ensure a tourist destination is suitable for visitors. Sometimes, disasters become one of the causes of failed destination management, as they render the area unsafe and uncomfortable. Therefore, a mitigation plan is necessary in tourist areas, making the mapping of existing tourist attractions crucial for disaster planning efforts. Desa Biting, Badegan, Ponorogo is a village with 9 (nine) tourist destinations, most of which are natural tourist attractions that have the potential to cause disasters. Given this situation, the disaster management team from Muhammadiyah University of Ponorogo, in collaboration with the village authorities, conducted several activities to create a disaster risk map. The methods used include: 1) conducting focus group discussions (FGD) with all stakeholders to discuss disaster potential, 2) conducting disaster mapping by identifying disaster-prone areas, 3) establishing a disaster response task force by leveraging existing institutional frameworks, and 4) installing disaster maps in tourist areas. From these activities, three dominant potential hazards were identified, namely forest fires, landslides, and floods. Based on the mapping results, mitigation efforts can be carried out to complement the organisational structure and supporting infrastructure. We recommend conducting a study on institutional readiness in preparing for disasters.